The Willing Horse: A Novel - Hay, Ian, 1876-1952 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Willing Horse: A Novel" by Ian Hay is a fictional work written in the early 20th century. The story seems to explore themes related to the aftermath of World War I, particularly focusing on the societal shifts and personal relationships formed during and after the conflict. It introduces characters such as Tom Birnie, a landlord with political radicalism and a complex love life, and his wife Diana, as well as their son Roy and childhood friend Eric Bethune, setting the stage for a narrative that likely intertwines personal grievances with larger historical events. The opening of the novel presents a colorful tapestry of life in a rural Scottish community on a Sunday morning, where the central character, a visitor to Baronrigg, reflects on the behavior, relationships, and dynamics of those attending church services. The text portrays a humorous yet critical view of societal norms and expectations, as Tom Birnie's radicalism clashes with the conservative values of his peers. The narrator's observations about Tom, his wife, and their guests hint at underlying tensions, romantic histories, and the weight of wartime experiences. As the congregation gathers, themes of duty, identity, and the lingering effects of war begin to emerge, promising deeper explorations of these characters' lives in the context of changing societal values brought about by the war. (This is an automatically generated summary.)
Release date is 2014-08-09
Produced by Al Haines
Keywords: World War, 1914-1918 -- Fiction